Memoria social del barrio Atucucho. - López Quiroz, Josselyn Lizbeth (2018)
For years, social memory has identified cities and neighborhoods. In this investigation we will analyze the case of the Atucucho neighborhood, which was constituted in the decade of the 1980s after an invasion of land by the Ministry of Health, after a great confrontation between the migrants and the army. The inhabitants who have lived in Atucucho have faced the oblivion of society and exclusion by the State. Despite certain shortcomings, the residents of the neighborhood are happy people and very proud of their houses because they were made thanks to the determination and courage of each man and woman. Another identifying element of this community is the union that was established from the beginning between the components of the neighborhood and with which day to day they formed what is now the territory of Atucucho. The constitution and the course of Atucucho have not always been easy, rather. The lack of presence of public institutions, directed to the care and safety of the inhabitants of the neighborhood, has turned this sector into a vulnerable territorial reality. In spite of all this, the inhabitants look for a way of overcoming and the way that their dreams and their history do not remain in the forgetfulness, that their triumphs are of reference, not only to the new generations of the surrounding neighborhoods, but also for the State.